Detectives and technological frames: integrating technology and social media into everyday work - Dewald, Stacy (Policing and society, 2023)
Technology and social media have increasingly transformed contemporary policing. Yet, scarce research explores how detectives view and use technology and social media in their everyday work. This study of a mid-sized American police department fills this gap in research by exploring how technological frames inform how detectives use technology and social media. First, detectives view technology and social media as tools, yet acknowledge the barriers inherent to using them (i.e. time-consuming). Therefore, the task at hand will determine to what extent detectives use technology. Second, detectives embrace the use of technology and social media and use it more than just in their role as a crime fighter, as their job calls for them to handle a variety of tasks: (1) prioritising suicide threats; (2) acting as a school resource officer; and (3) conducting prostitution stings. I argue that technological frames can contribute to officers overcoming barriers inherent with using technology and social media and encourage proactive policing activities. The findings from this study bring about several practical and policy implications for police departments including how to adapt to technological barriers.